PENGARUH PENAMBAHAN PLASTIK HIGH DENSITY POLY ETHYLENE PADA LAPISAN PERKERASAN ASPAL BETON AC-BC - Rian Wanardi Eriyono; Imam Hagni Puspito (Jurnal Infrastruktur, 2017)
Increased population growth is accompanied by an increase in the volume of traffic. These conditions must be supported by good pavement quality. Bending hardening is the most preferred pavement on highway pavement structures. A common way to increase asphalt quality to repair damage is by adding additives, one of them is plastic. This research tries to use additives in the form of High Density Poly Ethylene plastic seed which is expected to add stability value and even able to overcome the weakness of asphalt pavement asphalt pavement layer against damage. This study used an experimental method to obtain a comparison result between normal asphalt mixture and HDPE-asphalt plastics, it will be seen that the utilization of HDPE plastic seed will influence the characteristics of concrete asphalt mixture with variation of plastic addition of 3% and 6% calculated from the asphalt weight of the plan. From the analysis of normal asphalt mixture and asphalt mixture of HDPE 3% and 6% asphalt found the optimum asphalt content (KAO) that test results obtained values of mixed characteristic parameters for the normal mixture of VIM (4.46%), VMA (16.42%), VFB (72.78%), Stability (1155 Kg), Flow (3.56 Mm), MQ (325 Kg / mm); HDPE plastic meet the specification of Bina Marga 2010 revision III that is 5.9%, 5% and 5.8%. From the analysis process of Marshall asphalt mixture 3% VIM (3.98%), VMA (14.67%), VFB (72.88%), Stability (1417 Kg), Flow (3.49 mm), MQ (406 Kg / mm ) And HDPE 6% mixture of HDPE 6% VIM (3.71%), VMA (15.60%), VFB (76.28%), Stability (1408 Kg), Flow (3.71 mm), MQ (379, 60 Kg / mm). Overall on the stability value with the added 3% and 6% HDPE plastic content, the stability value of the normal asphalt value increases.